Electric-field-induced healing of inanimate topographies: Multistate resistive switching and nano-sized artificial synapse functionality - Kumar, Mohit; Lim, Jaeseong; Park, Ji Yong; Kim, Sangwan; Seo, Hyungtak (Applied Surface Science, 2020)
Formation and dissolution of conductive channels under the influence of applied electric field is widely considered key driver of resistive switching phenomenon, and vital for the emerging development of artificially intelligent synapses. Therefore, a comprehensive understanding of channel formation and knowledge of its real-time dynamics are crucial for conducting engineering at the device level. However, both concepts are poorly understood, especially for oxide-based devices. In this study, we demonstrate that inanimate topographies can be activated for charge transport in a NiO/ZnO heterojunction system by increasing the magnitude of the applied stress or by increasing its duration, which is responsible for multilevel memory storage. The formation and real-time dynamics of localized conducting channels (size > 35 nm) were revealed through current maps obtained using conductive atomic force microscopy. Additionally, bio-synaptic behaviors were mimicked at the nanoscale by applying electrical pulses. Furthermore, Kelvin probe force microscopy was used to confirm nanoscale variations in surface potential, which were attributed to localized defect variations and are responsible for spatial current variation. This study provides an essential breakthrough in enhancing our understanding of nanoscale conductive channel formation, and in doing so, it paves the way for the development of ultrahigh density nonvolatile storage memory applications.
Keywords: Artificial synapse; Conducting channels; Conductive atomic force microscopy; Conductive channels; Electric field induced; Kelvin probe force microscopy; Memory applications; Resistive switching; Artificial synapse; Conductive atomic force microscopy; Multistate; Nano-sized; Resistive switching